Effect of Chronic Digoxin Use on Mortality and Heart Failure Hospitalization in Pulmonary Arterial Hypertension - Kevin Y. Chang; Katherine Giorgio; Katlin Schmitz; Rob F. Walker; Kurt W. Prins; Marc R. Pritzker; Stephen L. Archer; Pamela L. Lutsey; Thenappan Thenappan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Digoxin acutely increases cardiac output in patients with pulmonary arterial hypertension (PAH) and right ventricular failure; however, the effects of chronic digoxin use in PAH are unclear. Methods and Results Data from the Minnesota Pulmonary Hypertension Repository were used. The primary analysis used likelihood of digoxin prescription. The primary end point was a composite of all‐cause mortality or heart failure (HF) hospitalization. Secondary end points included all‐cause mortality, HF hospitalization, and transplant‐free survival. Multivariable Cox proportional hazards analyses determined the hazard ratios (HR) and 95% CIs for the primary and secondary end points. Among 205 patients with PAH in the repository, 32.7% (n=67) were on digoxin. Digoxin was more often prescribed to patients with severe PAH and right ventricular failure. After propensity score‐matching, 49 patients were digoxin users, and 70 patients were nonusers; of these 31 (63.3%) in the digoxin group and 41 (58.6%) in nondigoxin group met the primary end point during a median follow‐up time of 2.1 (0.6–5.0) years. Digoxin users had a higher combined all‐cause mortality or HF hospitalization (HR, 1.82 [95% CI, 1.11–2.99]), all‐cause mortality (HR, 1.92 [95% CI, 1.06–3.49]), HF hospitalization (HR, 1.89 [95% CI, 1.07–3.35]), and worse transplant‐free survival (HR, 2.00 [95% CI, 1.12–3.58]) even after adjusting for patient characteristics and severity of PAH and right ventricular failure. Conclusions In this retrospective, nonrandomized cohort, digoxin treatment was associated with greater all‐cause mortality and HF hospitalization, even after multivariate correction. Future randomized controlled trials should assess the safety and efficacy of chronic digoxin use in PAH.